Hypomyelination, Hypodontia, Hypogonadotropic Hypogonadism (4H) Syndrome With Vertebral Anomalies: A Novel Association. (June 2015) - Muthusamy, Karthik; Sudhakar, Sniya V.; Yoganathan, Sangeetha; Thomas, Maya Mary; Alexander, Mathew
Hypomyelination, hypodontia, hypogonadotropic hypogonadism (4H) syndrome is a rare hypomyelination disorder with around 40 cases reported worldwide. Children with hypomyelination, hypodontia, hypogonadotropic hypogonadism syndrome present with varying degrees of developmental delay with a spastic ataxic syndrome with delayed eruption of teeth along with disruption in the eruption sequence, hypogonadotropic hypogonadism, and a fluctuating clinical course with intercurrent infections and varying periods of stability. The disorder is caused by mutations in POL3A and POL3B genes and is collectively termed as pol III–related leukodystrophies. Here we describe 2 children with hypomyelination, hypodontia, hypogonadotropic, hypogonadism syndrome and the association of multiple vertebral fusion anomalies in one of them, which has not been previously described in the literature. We conclude that the spectrum of the disorder is not limited to brain parenchyma alone and involves all the structures arising from neural ectoderm, and this needs further research.